The Functions of Discourse Markers in Newspaper Text - Sultonova Charos Iskandar qizi (Genius Publishing Group, 2022)
The article deals with the functions of discourse markers in newspaper text. This study is determined by the need for a comprehensive description of discursive markers as functional language units necessary to assess the connection of an utterance with a certain situation in the real world, and, more broadly, to ensure the coherence of the discourse as a whole.
Keywords: discursive markers; functions of discursive units; linguistic research; taxonomy of the functions